2007
DOI: 10.1016/j.jacc.2007.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Catheter Ablation of Ventricular Tachycardia in Patients With Arrhythmogenic Right Ventricular Dysplasia/Cardiomyopathy

Abstract: Our study shows a high rate of recurrence in ARVD/C patients undergoing RFA of VT. This likely reflects the fact that ARVD/C is a diffuse cardiomyopathy with progressively evolving electrical substrate. Further studies are needed to define the precise role of RFA of VT in ARVD/C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
137
2
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(144 citation statements)
references
References 44 publications
2
137
2
3
Order By: Relevance
“…5,6) The pros and cons of the efficacy of RFCA with electroanatomic mapping to suppress VT were also reported. [19][20][21] We used electroanatomic mapping techniques in one patient to suppress frequent VT recurrence after RFCA and ICD therapies. We consider the efficacy of the electroanatomic mapping technique to be controversial.…”
Section: Discussionmentioning
confidence: 99%
“…5,6) The pros and cons of the efficacy of RFCA with electroanatomic mapping to suppress VT were also reported. [19][20][21] We used electroanatomic mapping techniques in one patient to suppress frequent VT recurrence after RFCA and ICD therapies. We consider the efficacy of the electroanatomic mapping technique to be controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, RFA can be considered as an adjuvant therapy to ICD placement in patients with VT or frequent ICD firing despite using BB or antiarrhythmic drugs or in patients who were not able to tolerate ARVC recommended medications (class I) [22]. Furthermore, multiple electrophysiologic mapping techniques have been used to treat VA including voltage mapping and substrate mapping [31,32,4648]. …”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…Combined endocardial–epicardial VT ablation has had significant short- and long-term success rates compared to endocardial VT ablation alone [22,49]. VT recurrence following VT ablation could be explained by the patchy nature of ARVC; hence, development of new arrhythmic foci is not infrequent [32,50,51]. Therefore, RFA is currently not recommended as stand-alone therapy or as an alternative to ICD for ARVC patients due the progressive nature of ARVC (class III) [22].…”
Section: Radiofrequency Ablationmentioning
confidence: 99%
“…Although recent technological advances with electroanatomic and voltage mapping systems have significantly improved outcomes [27][28], catheter ablation can reduce the frequency of VT episodes, but long-term follow-up studies have demonstrated a risk of recurrence. However, only an endocardial approach was used in most of the cases previously reported [29][30][31].…”
Section: Arrhythmogenic Right Ventricular Cardiomyopathymentioning
confidence: 99%